Dealloying/exsolution-induced nanoporous perovskite oxides anchored with alloy nanoparticles for the oxygen evolution reaction. Issue 4 (4th January 2023) - Cui, Yu; Chao, Yang; Lin, Jianbin; Ke, Wenxue; He, Xin; Chen, Mei; Zhang, Chi
Abstract : The exsolution of dealloying/annealing-derived nanoporous La0.9 Co x Fe1− x O3 generated Co–Fe nanoparticle-anchored perovskite hybrids. The exsolved perovskite oxides present improved oxygen evolution reaction activity. Abstract : Compositional design and surface decoration are generally utilized to develop efficient perovskite oxide-based electrocatalysts for the oxygen evolution reaction (OER). Surface decoration via in situ exsolution of metal or alloy nanoparticles on the perovskite oxides' surface has been reported as an efficient approach to enhance the OER activity. However, the perovskite oxides prepared for exsolution fabricated by solid-state reactions have limited surface areas. In this work, nanoporous La0.9 Co x Fe1− x O3 ( x = 0, 0.1, and 0.2) are fabricated by dealloying and annealing approaches. The nanoporous perovskites are exsolved in a 5 vol% H2 /Ar atmosphere to form Fe or Co x Fe y nanoparticles on the surface. The results reveal that exsolution promotes OER performance. The Co contents and surface oxygen vacancies are also associated with the OER activity. For the reduced La0.9 Co0.2 Fe0.8 O3 (R-LCF28), an overpotential of 352 mV with a Tafel slope of 62.10 mV dec −1 is achieved, which is 72 mV lower than that of the un-reduced LCF28. The stability test proves that R-LCF28 also has better stability than reduced La0.9 Co0.1 Fe0.9 O3 (R-LCF19). This work demonstrates that nanoporous perovskite oxides with alloy nanoparticles anchored on the surface can be fabricated via dealloying combined with annealing and exsolution methods.